Wage policy of medium and large Portuguese firms - Suleman, F.; Lagoa, S.; Suleman, A.; Pereira, M. L. (Portuguese Journal of Social Science, 2013)
The research on wage policies has been triggered by the interest in identifying whether labour market or institutional forces shape wage settings inside firms. This article draws on linked employer-employee data and uses a fuzzy c-means clustering analysis to identify the typical wage policies of medium and large firms in Portugal. Empirical evidence suggests firms are segmented into four clusters that can be labelled according to wage rules as regulated, asymmetric, hierarchical and discretionary. The first two clusters comprise low wage firms, and are highly responsive to market conditions. The firms belonging to the latter clusters take advantage of discretionary power to differentiate the workforce. Our findings therefore illustrate different dimensions of wage flexibility. Furthermore, we found that employment flexibility and wage adjustments can co-exist, and this affects female, young and blue-collar workers in particular.